ANTECEDENTS OF INTRINSIC MOTIVATION, METACOGNITION AND THEIR EFFECTS ON STUDENTS’ ACADEMIC PERFORMANCE IN FUNDAMENTAL KNOWLEDGE FOR MATRICULATION COURSES (Malaysian Journal of Learning and Instruction, 2017)
Purpose - This study examined the interrelationships between a set of antecedent academic intrinsic motivations and metacognitive strategy such as goal orientation, perceived value and religiosity in Fundamental Knowledge for Matriculation courses (FKM). It also investigated the relationship between intrinsic motivation and metacognitive strategy on one hand, and studentsâ€™ academic performance on the other. Methodology â€“ A total of 471 second-year students (233 males and 238 females) were randomly selected to participate in a survey, following a stratified random sampling. Hypothesized relationships of academic intrinsic motivation, metacognitive strategy and their predictors were then tested by using Structural Equation Modeling. Findings - Using bootstrapping (data-based resampling), the findings confirmed the proposed model which suggests that goal orientation and perceived values contributed to studentsâ€™ academic performance directly and indirectly via intrinsic motivation and metacognition. Additionally, the findings also indicate that goal orientation was the main determinant of intrinsic motivation and metacognition, followed by perceived value. It was also found that religious motives within a perceived value construct contributed  significantly to studentsâ€™ academic performance in a direct and indirect manner via intrinsic motivation and metacognitive strategy. Significance â€“ The study suggests the importance of goal orientation especially mastery and performance as well as perceived value and most significantly, religious motive in studentsâ€™ intrinsic motivation and their use of metacognitive strategies. The study also highlights the significance of intrinsic motivation and metacognitive strategies in studentsâ€™ academic performance. Hence, it is recommended that learners should be helped to adopt appropriate academic goals, and be encouraged to use metacognitive strategies to enhance their learning attainments.